Liquid Water Characteristics in the Compressed Gradient Porosity Gas Diffusion Layer of Proton Exchange Membrane Fuel Cells Using the Lattice Boltzmann Method - Song Yan; Mingyang Yang; Chuanyu Sun; Sichuan Xu (Energies, 2023)
The mitigation of water flooding in the gas diffusion layer (GDL) at relatively high current densities is indispensable for enhancing the performance of proton exchange membrane fuel cells (PEMFCs). In this paper, a 2D multicomponent LBM model is developed to investigate the effects of porosity distribution and compression on the liquid water dynamic behaviors and distribution. The results suggest that adopting the gradient GDL structure with increasing porosity along the thickness direction significantly reduces the breakthrough time and steady–state total water saturation inside the GDL. Moreover, the positive gradient structure reaches the highest breakthrough time and water saturation at 10% compression ratio (CR) when the GDL is compressed, and the corresponding values decrease with further increase of the CR. Considering the breakthrough time, total water saturation and water distribution at the entrance of the GDL at the same time, the gradient structure with continuously increasing porosity can perform better water management capacity at 30% CR. This paper is useful for understanding the two–phase process in a gradient GDL structure and provides guidance for future design and manufacturing.